Arguing it out discussion in twelfth-century Byzantium - Cameron, Averil 1940- (The Natalie Zemon Davis Annual Lecture series at Central European University, Budapest, 2016)
"The social and cultural history of Byzantium seems at first sight unsuited to the kind of thick description at which Natalie Zemon Davis excels. Yet recent scholarship that aims to locate Byzantine culture and society within new global and transnational approaches to history demands a more nuanced understanding. In these lectures she will explore the question of what kind of thick description can be provided. She will focus on the long twelfth century, a time of intense creativity as well as of rising tensions, and one for which literary approaches are currently a lively area in current scholarship. She will argue for their integration within a broader approach to Byzantine social and cultural history focusing on discourse, and drawing on the many kinds of dialogue texts (secular and religious) that were a key feature of Byzantine textual production"...From publisher's website